2010
DOI: 10.1111/j.1751-1097.2010.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Occurrence of Energy Transfer and Photoinduced Electron Transfer in Interactions of Hen Egg White Lysozyme with 4‐Nitroquinoline‐1‐Oxide

Abstract: The carcinogenic drug 4-nitroquinoline-1-oxide (4NQO) has been found to bind with the protein hen egg white lysozyme as evident from fluorescence quenching experiments. The binding constant and stoichiometry have been determined. The values of the thermodynamic parameters indicate that the interaction is an enthalpy-driven spontaneous phenomenon. The experimental value of change in free energy is similar to that obtained from the docking study. The far UV circular dichroism spectra show some changes in the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 41 publications
0
5
1
Order By: Relevance
“…52 A similar case of absence of MF effect is also obtained by our group while studying the interaction of 4-nitroquinoline-1-oxide and hen egg white lysozyme as the donor-acceptor separation distance is about 3.1 Å, which inhibits spin conversion. 60 On the contrary, in the present case of AD-HSA system the separation distance (13.5 Å) between the donor and the acceptor moieties of PET is tting for appreciable MF effect. Our previous report shows that during interaction with HSA, two other acridine derivatives, viz.…”
Section: Discussioncontrasting
confidence: 54%
“…52 A similar case of absence of MF effect is also obtained by our group while studying the interaction of 4-nitroquinoline-1-oxide and hen egg white lysozyme as the donor-acceptor separation distance is about 3.1 Å, which inhibits spin conversion. 60 On the contrary, in the present case of AD-HSA system the separation distance (13.5 Å) between the donor and the acceptor moieties of PET is tting for appreciable MF effect. Our previous report shows that during interaction with HSA, two other acridine derivatives, viz.…”
Section: Discussioncontrasting
confidence: 54%
“…With the help of K SV and fluorescence lifetime (τ 0 ) values, a k q value has been determined from eq 4 which is 1.449 × 10 12 M −1 s −1 . The upper limit of k q is 10 10 M −1 s −1 for a diffusion control phenomenon from eq 5, 31 which indicates that the quenching is static in nature, suggesting the formation of a ground state complex.…”
Section: Resultsmentioning
confidence: 98%
“…Tyr and Trp, the aromatic amino acid residues of proteins, are prime targets for oxidation by various forms of reactive oxidative species (ROS) . Previous reports indicated that Lyso could be attacked by ROS via the interaction of ROS with its Tyr and Trp residues . The ability of ATRA •+ to react with Tyr and Trp was evaluated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the potential of ATRA •+ to damage biomolecules, we herein investigated the interactions of ATRA •+ with Lyso and two amino acids. Lyso was chosen as a model protein because of its extensive use in the studies of photodamage of proteins (35)(36)(37)(38)(39)(40). Result shows that the decay of ATRA •+ at 590 nm is accelerated by the presence of Lyso at pH 7.4, indicating that ATRA •+ can interact with Lyso (Fig.…”
Section: Reactions Of Atra •+ With Lysozyme and Amino Acidsmentioning
confidence: 99%